Analysis Of The Economic Dimension Sustainability Of The Na-Oogst Tobaccco Business In Jember - nila afila; Muksin Muksin; Ujang Suryadi (Badan Penerbitan Fakultas Pertanian (BPFP), Universitas Bengkulu, 2020)
Na-oogst tobacco commodity is an export commodity that has a role in increasing national income through excise tax. Many factors can influence the decision of farmers to conduct tobacco cultivation in the midst of enormous pressure on tobacco products. This study aims to analyze the economic dimension sustainability of the na-oogst tobacco business in Jember. The metodology used is Multi Dimensional Scaling (MDS) to analyze sustainability by using 10 atributs. The results of the analysis of the economic dimension show that the na-oogst tobacco business in Jember is categorized as